Lightning Risk Assessment, Control and Protection Scheme Design for a Rooftop Photovoltaic System in the New Capital of Egypt - Omar, Ahmed I.; Abd-Allah, M. A.; Shokry, Ahmed; Said, Abdelrahman (International Journal of Robotics and Control Systems, 2024)
The absence of an effective lightning protection system for photovoltaic (PV) systems can hinder their integration into networks. Outdoor PV installations are vulnerable to direct or indirect lightning strikes, resulting in damaging overvoltages that harm the PV structure. These systems, often situated on rooftops or open fields, face increased lightning strike risks due to their exposure compared to more sheltered setups. Lightning-induced surges can harm sensitive electrical components like panels, inverters, and wiring, leading to potential damage and downtime. The complexity of PV systems, with interconnected components, makes designing protection strategies challenging. Compliance with lightning protection standards is crucial to prevent damage, downtime, and financial losses. Implementing effective protection measures involves grounding, surge protection, and adherence to regulations. Lightning protection systems intercept strikes and safely direct electrical energy to the ground, safeguarding sensitive components and ensuring continuous power generation. The IEC 62305-2 standard guides lightning risk assessment and mitigation, aiding in evaluating risks, calculating damage likelihood, and designing protective measures. A case study focusing on the Arab African International Bank's rooftop PV system in Egypt illustrates the importance of lightning risk management in financial, operational, and regulatory contexts for solar projects. Risk assessment aims to identify vulnerabilities, implement mitigation strategies, and ensure safe, reliable system operation. By addressing lightning risks effectively, stakeholders can enhance system safety, reliability, and longevity while minimizing downtime and revenue loss associated with lightning strikes.